A religiosidade e o homem amazônida: a construção da subjetividade a partir de sua prática religiosa nos cultos de Matriz Africana - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
The search for the sacred, always, was made present in the man's life that was returned the practice of his/her religiosity or spirituality, therefore the religious phenomenon through the mystic search and of the practice of the syncretism that involves a miscellany of practices and rituals that seek to provide the subject's wellbeing it permeates the context of the human civilization and it would not be different in the area that we inhabited, however how to understand the proximity of a religious practice which we didn't have extreme approach, as this man builds his or her subjectivity with base in practices so different from his or her culture. This investigation intended the investigation of as the man amazônida, in specific the one of Amazon, builds its subjectivity starting from the contact with the cults of African head office, tends as analysis base Martin Heidegger's philosophy. It’s a qualitative research nature and it developed starting from the concepts proposed by the phenomenology that looks for to do the understanding of the other starting from his/her speech. The method was the research phenomenological in Psychology and the phenomenological interview was used made with 11 participants of religious practices guided by the Federation of Umbanda and Cults of Head office Brazilian Afro of the State of Amazon - FUCABEAM, and the data were collected after the approval of the research project by the committee of ethics of UFAM, authorization of the institution and signature of the term of free and illustrious consent for the participants. The data were collected starting from interview audio recorded with a duration on average of 30 minutes at two hours each in the period of March to August of 2015 starting from the guiding question: I would like that you would describe how was your first relationship with the candomblé (or Umbanda) and how did you feel about your entrance for the religion? About these speeches were identified Units of meanings that allowed the formation of Categories of Analysis that were for the understanding of as the individuals they constituted of his/her subjectivity starting from the practices with the cults of African head office. The study revealed that the practicing individuals of the cults of head office African Umbanda and Candomblé constitute the subjectivity ruled in a process of take care-pity-other or be-with-the-other in a proposal that taking care of the other this being takes care of itself own. I notice that in the historical path, each one of them went diving in the knowledge concerning the religions of African head office that profess and the humor state propitiated the understanding of their role, of their possibilities, of their canbeing. As the same time other way of existence is made present, the interpretation that Heidegger (2009, p. 204). The understands as the "elaboration of the possibilities projected in the understanding". The Settles down the indication of what and what for something, revealing the sense. The sense of be-member of religion of African head office; the sense of assuming the characteristics of their masters' personality or guides; the sense for the factuality lived daily that resulted in to be who they are today, their temples leaders, taking the responsibility for each one of those that seek them, in the objective of defend knowledge, relief, care.
Keywords: Religião; Religiosidade; Fenomenologia; Religion; Religiosity; Phenomenology; CIÊNCIAS HUMANAS: PSICOLOGIA